A method for the preliminary design of gears using a reduced number of American Gear Manufacturers Association (AGMA) correction factors. Issue 4 (3rd April 2017) - Gautham, B.P.; Kulkarni, Nagesh H.; Panchal, Jitesh H.; Allen, Janet K.; Mistree, Farrokh
ABSTRACT: Typically, the preliminary design of mechanical components such as gears is carried out using standardized design processes such as those developed by the American Gear Manufacturers Association (AGMA). These design standards include a large number of 'correction factors' to account for various uncertainties. As the knowledge about these uncertainties increases, it becomes possible to include them systematically in the design procedure, thereby reducing the number of empirical correction factors. Robust design provides a way to design in the presence of various uncertainties. In this article, a design method is proposed to eliminate empirical correction factors and is demonstrated by eliminating two correction factors from the AGMA design standards for a spur gear, namely, the factor of safety in contact and the reliability factor by the formal introduction of uncertainty in the magnitude of load and material properties. The proposed method is illustrated with the design of an automotive gear with desired reliability, cost and robustness.